Opal-RT based Analysis and Implementation of DFIG with Standalone Wind Energy Conversion System - Gupta, Saurabh; C. Choube, S; Gupta, Sushma (International Journal of Engineering and Technology, 2018)
In this paper, the detailed analysis and performance of a vector oriented control topology in Doubly-Fed Induction Generator (DFIG)-based wind power generation systems is discussed in order to produce a high quality of output voltage. The distortion of voltage and frequency control capabilities in both stator side and rotor-side converters (SSC&RSC) for unbalanced network condition are investigated. The control scheme is implemented in the synchronous rotating reference frame and provides specific current control for both the SSC and RSC. The primary objective of the control scheme is to maintain constant voltage and frequency under variable wind speed and operating conditions of load. Thus this technique is found to be capable of achieving minimum harmonic voltage distortion, thereby resulting in a nearly sinusoidal waveform to improve the power quality of the systems. The performance of the suggested topology is validated in real time environment using Opal-RT Lab simulator and adequate results were taken.Â Â